Analysis, modeling, and implementation of a new transformerless semi‐quadratic Buck–boost DC/DC converter. (4th March 2019) - Hasanpour, Sara; Mostaan, Ali; Baghramian, Alfred; Mojallali, Hamed
Summary: This paper presents a novel transformerless semi‐quadratic buck‐boost converter (SQBuBoC). In the proposed SQBuBoC, two power switches with simultaneous operation are used and a higher step‐up/step‐down voltage conversion ratio is achieved compared with the traditional buck‐boost, Cuk, single‐ended primary‐inductor converter, and Zeta converters. The positive polarity of the output voltage, along with low ripple continuous input current and common ground between the source and the output voltages, are some features that make the suggested topology more suitable for many applications with wide range of output voltage such as photovoltaic systems. Moreover, the total voltage stress across the power switches in this converter is lower than the cascade boost, and the traditional buck‐boost converters led to power MOSFETs selection with lower drain‐source ON resistance (Rds ) and efficiency improvement. All the steady‐state analysis and comparisons in continuous conduction mode (CCM) are discussed in details. In addition, to study the low frequency behavior of the SQBuBoC by means of the state‐space averaging technique, the small and large signal models of this converter in CCM are presented. Finally, the SQBuBoC analysis is justified using experimental results of a 50 W step‐up 25 V to 120 V and a 28 W step‐down 25 V to 14 V laboratory prototypes. Abstract : In this paper, a new configuration of non‐isolated doubled‐switch buck‐boost converter (SQBuBoC) is presented. Continues input current with low ripple, semi‐quadratic high step‐up and step‐down voltage conversion ratio with wide range of the output voltage, simple structure, noninverting voltage conversion ratio, and common ground between input and output voltages are the substantial merits of the proposed SQBuBoC. Furthermore, because of the low‐voltage stress across the power switches, the power losses are decreased, which lead to efficiency improvement.